2010
DOI: 10.1007/s10562-010-0268-5
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-Modified Mesoporous Ni–Mg–Al Mixed Oxides for Partial Oxidation of Methane

Abstract: Fluorine-modified Ni-Mg-Al mixed oxides prepared by thermal decomposition of hydrtalcite-type (HT) precursor was characterized by XRD, EXAFS, TGA, SEM, TPD-CO 2 , TPR-H 2 , N 2 adsorption/desorption technique, and then tested in the partial oxidation of methane (POM). The result revealed that fluorine was successfully introduced into Ni-Mg-Al mixed oxide via the high dispersion of MgF 2 , which led to the formation of the periclase-type catalyst with mesoporous structure. By compared with pure Ni-Mg-Al mixed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Similar results were obtained by Zhang et al [64]. They stated that 6.5 mol % La was suitable, and 99% of CH 4 conversion, 93% of CO selectivity and 96% of H 2 selectivity could be achieved at 1,053 K. Fluorine element could also be introduced to Ni-Mg-Al hydrotalcite [65] to modify the basic properties of catalyst. Evaluation in POM revealed that, such a catalyst was stable without deactivation after 120 h life-test at 1,053 K. Trace amount of noble metals were also effective in reducing carbon deposition on Ni-Mg-Al hydrotalcite [66].…”
Section: Hydrotalcite Typesupporting
confidence: 82%
“…Similar results were obtained by Zhang et al [64]. They stated that 6.5 mol % La was suitable, and 99% of CH 4 conversion, 93% of CO selectivity and 96% of H 2 selectivity could be achieved at 1,053 K. Fluorine element could also be introduced to Ni-Mg-Al hydrotalcite [65] to modify the basic properties of catalyst. Evaluation in POM revealed that, such a catalyst was stable without deactivation after 120 h life-test at 1,053 K. Trace amount of noble metals were also effective in reducing carbon deposition on Ni-Mg-Al hydrotalcite [66].…”
Section: Hydrotalcite Typesupporting
confidence: 82%
“…The results revealed that fluorine was successfully introduced into Ni-Mg-Al mixed oxide via the high dispersion of MgF 2 . Such catalysts showed a high performance over POM without deactivation even after 120 h run at 1023 K. This could be reasonably attributed to the promotional effect of the F-anions, which improved the homogeneous distribution of nickel and basicity of the catalyst with high resistance to coking and sintering [56]. By repeated "calcination-reconstruction" cycles, transition metals (Cr, Fe, Co, Ni and Cu) were introduced with ruthenium into layered double hydroxide structure.…”
Section: Hydrotalcite Precursorsmentioning
confidence: 97%
“…Increasing the silicate load resulted in a decrease of the specific surface area and the Ni dispersion. Moreover, the samples with large silicate content were deactivated by oxidation of metallic nickel particles [56]. Hydrotalcite structure also allows the introduction of promoters, such as halogens.…”
Section: Hydrotalcite Precursorsmentioning
confidence: 99%
“…When layered double hydroxides are modified by SDS, their crystallinity is decreased and morphology is less uniform . In addition, the incorporation of Zn might make the structure of NiAl layered double hydroxides occur as re‐combination . Fig.…”
Section: Resultsmentioning
confidence: 99%